MENINGKATKAN PENGETAHUAN, SIKAP DAN PERILAKU ANAK SD DARUL FADHLI PALEMBANG DALAM PENCEGAHAN PENYAKIT DIARE - Ahmad Ghiffari; Budi Utama; Indri Ramayanti; Tasya Aulia Dita (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
The incidence of diarrhea in Indonesia was 3.0% in children aged 5-14. The incidence of diarrhea in South Sumatra in 2017 reached 174,808 and has increased to 94,563 million every year. The behavior of washing hands with soap, especially after contact with feces, can reduce the incidence of diarrhea by 42-47%. Snacks pose a risk to health because their handling is often unhygienic, contaminating the snacks. This activity aims to educate children about the relationship between personal hygiene and snack consumption patterns with diarrhea. This activity observed 57 students of SD Darul Fadhli Palembang. This activity concludes that there is an increase in personal hygiene, snack consumption patterns, and the knowledge of diarrhea. It is recommended that schools pay more attention to children during snack time and collaborate with health centers for routine counseling about diarrheal diseases and their prevention